Recovery From Eccentric Squat Exercise in Resistance-Trained Young and Master Athletes With Similar Maximum Strength: Combining Cold Water Immersion and Compression - Schmidt, Julian; Ferrauti, Alexander; Kellmann, Michael; Beaudouin, Florian; Pfeiffer, Mark; Volk, Nicola Reiner; Wambach, Jan Martin; Bruder, Oliver; Wiewelhove, Thimo (Frontiers in Physiology, 2021)
The aim of this study was to investigate whether recovery from eccentric squat exercise varies depending on age and to assess whether the use of a mixed-method recovery (MMR) consisting of cold water immersion and compression tights benefits recovery. Sixteen healthy and resistance-trained young (age, 22.1±2.1years; N=8) and master male athletes (age, 52.4±3.5years; N=8), who had a similar half squat 1-repetition maximum relative to body weight, completed two identical squat exercise training sessions, separated by a 2-week washout period. Training sessions were followed by either MMR or passive recovery (PR). Internal training loads [heart rate and blood lactate concentration (BLa)] were recorded during and after squat sessions. Furthermore, maximal voluntary isometric contraction (MVIC) force, countermovement jump (CMJ) height, resting twitch force of the knee extensors, serum concentration of creatine kinase (CK), muscle soreness (MS), and perceived physical performance capability (PPC) were determined before and after training as well as after 24, 48, and 72h of recovery. A three-way mixed ANOVA revealed a significant time effect of the squat protocol on markers of fatigue and recovery (p<0.05; decreased MVIC, CMJ, twitch force, and PPC; increased CK and MS). Age-related differences were found for BLa, MS, and PPC (higher post-exercise fatigue in younger athletes). A significant two-way interaction between recovery strategy and time of measurement was found for MS and PPC (p<0.05; faster recovery after MMR). In three participants (two young and one master athlete), the individual results revealed a consistently positive response to MMR. In conclusion, master athletes neither reach higher fatigue levels nor recover more slowly than the younger athletes. Furthermore, the results indicate that MMR after resistance exercise does not contribute to a faster recovery of physical performance, neuromuscular function, or muscle damage, but promotes recovery of perceptual measures regardless of age.